The impact of applying corporate governance standards on the performance of workers in the government health sector in Najran region - Al-Yami, Dahen Mohammed Zyad; Al-Sawat, Talak Awad Mohammed (Journal of Economic, Administrative and Legal Sciences, 2022)
The current study aims mainly to identify the impact of the application of governance standards on the performance of workers in the health sector. To achieve the objectives of the study, the descriptive analytical approach was used in preparing the study, in addition to the use of the questionnaire tool in collecting data. The study was applied to a sample of (295) employees working in the government health sector in Najran region. After collecting the data, the (SPSS V23) program was used. in the data analysis process. The study reached a number of results, the most important of which are: There is a high level of application of governance standards in the government health sector in Najran with a percentage of (76.5%), and the results showed a high degree of effectiveness for the performance of workers in the health sector with a percentage of (79.9%). The results also showed a statistically significant effect at the level of significance (α≤0.05) for the dimensions of governance (transparency, responsiveness, rule of law, justice, accountability) on the performance of workers in the government health sector in Najran region. In light of these results, the study recommended a number of recommendations, most notably: The regulations within health institutions that stipulate strict laws and rules to punish those who are not disciplined in their work hours or when providing services must be strengthened. Increasing the percentage of appointment of reliable and experienced health service providers in the government health sector in Najran.